2013
DOI: 10.1007/s10103-013-1283-8
|View full text |Cite
|
Sign up to set email alerts
|

Study of photodynamic therapy in the control of isolated microorganisms from infected wounds—an in vitro study

Abstract: The effective treatment of infected wounds continues to be a serious challenge, mainly due to the rise of antibiotic-resistant bacteria. Photodynamic therapy (PDT) refers to the topical or systemic administration of a non-toxic, photosensitizing agent (PS), followed by irradiation with visible light of a suitable wavelength. The possibility of applying the PDT locally is what makes it so favorable to the treatment of infected wounds. The goal of this study was to evaluate the action of the PDT in the inactivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…The tested microorganisms were mostly obtained from American Type Culture Collection but in some cases pathogens, especially S. aureus , were isolants or clinical strains (Table 1). 60,195,210,211,251,363,421,461 Several studies focused on APDT of oral microflora, in particular, bacteria found in dentin, usually isolated from patients with deep caries lesions 153,216,257,263,282,284,362,385…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tested microorganisms were mostly obtained from American Type Culture Collection but in some cases pathogens, especially S. aureus , were isolants or clinical strains (Table 1). 60,195,210,211,251,363,421,461 Several studies focused on APDT of oral microflora, in particular, bacteria found in dentin, usually isolated from patients with deep caries lesions 153,216,257,263,282,284,362,385…”
Section: Resultsmentioning
confidence: 99%
“…The tested microorganisms were mostly obtained from American Type Culture Collection but in some cases pathogens, especially S. aureus, were isolants or clinical strains (Table 1). 60,195,210,211,251,363,421,461 Several studies focused on APDT of oral microflora, in particular, bacteria found in dentin, usually isolated from patients with deep caries lesions 153,216,257,263,282,284,362,385 Some studies also investigated MB-APDT targeted towards viruses, including vesicular stomatitis virus (VSV), bovine viral diarrhea virus (BVDV), dengue virus, West Nile virus (WNV), hepatitis C virus (HCV), herpes simplex virus type 1 (HSV-1) and SARS-CoV2. 215,297,299,300,311,314,321,331,403,408,409,411 Anti-parasitic photodynamic therapy investigations were dominated by Leishmania spp.…”
Section: The Targets Of Methylene Blue-mediated Antimicrobial Photoin...mentioning
confidence: 99%
“…Além da própria resistência intrínseca de cepas bacterianas a formação de espécies reativas de oxigênio, o comprimento de onda, intensidade de luz e fotossensibilizador utilizado, interferem ativamente em tal processo. [17][18][19] Por fim, foi possível notar que caso a quantidade de FS não seja suficiente para interação completa das bactérias existente no meio, a exposição isolada à fonte de energia pode causar efeito contrário e estimular a formação de novas colônias. Tal fato, quando avaliado isoladamente, pode causar desestimulo a sua utilização.…”
Section: Resultsunclassified
“…As PSs can potentially bind to many sites in the bacteria cell, the lethal oxidative damage caused by PDT is non-specific. This is important for activity against AMR pathogens and greatly reduces the likelihood of developing resistance, as confirmed by several laboratory experiments [ 93 , 94 , 95 ]. In addition, anionic or neutral PS also damage DNA strands, lowering thymidine incorporation during DNA synthesis [ 96 ].…”
Section: Strategies Under Investigation With Potential In Dfi Managementmentioning
confidence: 95%